Contexts as The Determining Roles of Javanese Phatic ‘Monggo’: Culture-Specific Pragmatics Perspective - Kunjana Rahardi (Indonesian Language Education and Literature, 2019)
Context is a very important aspect to determine speech intentions. Failure to describe contexts potentially causes misunderstanding. In a Javanese society, there is a phatic communion ‘monggo’ which has varied pragmatic meanings depending on contexts. The variety of meanings poses a potential problem for language learners. Considering this, a research is conducted to investigate how contexts become determining factors of pragmatic meanings of ‘monggo.’ The research data are excerpts of utterances containing phatic ‘monggo’. The data sources are the excerpts of utterance between the speaker and hearer having Javanese cultural backgrounds. The data are gathered using the observation method, by recording and note-taking as the basic and advanced techniques. The gathered data are classified carefully to be analyzed using the contextual identity analysis method. The research result shows the roles of contexts as follows: (a) determine the phatic meaning of ‘monggo’, (b) provide a background of the phatic meaning of ‘monggo’, (c) confirm the phatic meaning of ‘monggo’, and (d) describe the phatic meaning of ‘monggo.’ The pragmatic meanings of the phatic ‘monggo’ include: (a) inviting sincerely, (b) inviting hesitantly, (c) prohibition, (d) doubt, (e) excuse me, and (f) invitation.Konteks sangat penting dalam menentukan maksud pembicaraan. Kegagalan untuk menggambarkan konteks berpotensi menyebabkan kesalahpahaman. Dalam masyarakat Jawa, ada kata 'monggo' yang memiliki beragam makna pragmatis tergantung pada konteksnya. Keragaman makna menimbulkan masalah bagi pemelajar bahasa. Berdasarkan hal tersebut, penelitian ini dilakukan untuk menyelidiki konteks yang menjadi faktor penentu terhadap makna pragmatis dari 'monggo'. Data penelitian adalah kutipan dari ujaran yang mengandung kata ‘monggo'. Sumber data adalah kutipan dari ujaran antara pembicara dan pendengar yang memiliki latar belakang budaya Jawa. Data dikumpulkan dengan menggunakan metode observasi, dengan mencatat yang juga digunakan sebagai teknik dasar dan lanjutan. Data yang terkumpul diklasifikasikan dengan cermat untuk dianalisis menggunakan metode analisis identitas kontekstual. Hasil penelitian menunjukkan peran konteks, meliputi: (a) menentukan makna kata 'monggo', (b) memberikan latar belakang makna kata 'monggo', (c) mengonfirmasi makna kata 'monggo', dan (d) menguraikan makna kata 'monggo'. Adapun arti pragmatis kata 'monggo', yaitu: (a) mengundang dengan tulus, (b) mengundang ragu-ragu, (c) melarang, (d) keragu-raguan, (e) permohonan maaf, dan (f) undangan.